2022
DOI: 10.3389/fendo.2022.918899
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Ovarian Tissue Transplantation Outcomes by Ovarian Tissue Processing Size for Cryopreservation

Abstract: Ovarian tissue cryopreservation (OTC) is the only pre-treatment option currently available to preserve fertility for prepubescent girls and patients who cannot undergo ovarian stimulation. Currently, there is no standardized method of processing ovarian tissue for cryopreservation, despite evidence that fragmentation of ovaries may trigger primordial follicle activation. Because fragmentation may influence ovarian transplant function, the purpose of this systematic review was (1) to identify the processing siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 137 publications
1
14
0
Order By: Relevance
“…The method has been initially considered to hold an increased risk of unsuccessful subsequent ovarian tissue transplantation, as well as was believed to activate follicular development, thus compromising fertility success [ 47 ]. However, a recent systematic review showed promising results of ovarian tissue transplantation with regard to reproductive outcomes demonstrated by the restoration of ovarian function in up to 98% of the patients [ 48 ]. Pregnancy was achieved in over 80% of cancer-surviving patients undergoing ovarian tissue transplantation whereas the live birth rate reached 56% depending on the size of cryo-preserved ovarian tissue and the technique used for cryopreservation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been initially considered to hold an increased risk of unsuccessful subsequent ovarian tissue transplantation, as well as was believed to activate follicular development, thus compromising fertility success [ 47 ]. However, a recent systematic review showed promising results of ovarian tissue transplantation with regard to reproductive outcomes demonstrated by the restoration of ovarian function in up to 98% of the patients [ 48 ]. Pregnancy was achieved in over 80% of cancer-surviving patients undergoing ovarian tissue transplantation whereas the live birth rate reached 56% depending on the size of cryo-preserved ovarian tissue and the technique used for cryopreservation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent systematic review showed promising results of ovarian tissue transplantation with regard to reproductive outcomes demonstrated by the restoration of ovarian function in up to 98% of the patients [ 48 ]. Pregnancy was achieved in over 80% of cancer-surviving patients undergoing ovarian tissue transplantation whereas the live birth rate reached 56% depending on the size of cryo-preserved ovarian tissue and the technique used for cryopreservation [ 48 ]. Another study showed a live birth rate following ovarian tissue cryopreservation and subsequent transplantation in 21% of cancer survivors with the application of IVF treatment and in 33% of cancer survivors with spontaneously achieved pregnancy [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review on ovarian tissue processing size for cryopreservation evaluated 92 participants who underwent ovarian tissue transplantation. 36 The review reported a pregnancy rate of 81.3%, 45.5%, 66.7% and a live birth rate of 56.3%, 18.2%, 66.7% in the strip, square and fragments, respectively. This data has shown that ovarian tissue transplantation is no longer considered an experimental technique.…”
Section: Ovarian Tissue Cryopreservation In Vitro Maturation Of Oocytesmentioning
confidence: 97%
“…The goal of OTC is to maintain the morpho-functional characteristics of the ovary providing in this way a huge supply of primordial follicles, which can be successfully used in the future, preserving their fertility. Systematic reviews in regard to the clinical outcome of ovarian transplantation range between a minimum of 42% and a maximum of 81%, denoting the clinical importance of using this fertility cryopreservation method ( 127 , 128 ). Noteworthy, 130 healthy babies were born worldwide with the applied OTC ( 129 ) two women only worldwide have undergone transplantation with the OTC program which resulted in three live births after transplantation ( 130 , 131 ).…”
Section: Not Routinely Applied Assisted Reproductive Technologies For...mentioning
confidence: 99%